A COMPARATIVE STUDY OF THE PRODUCTION COSTS OF HYDROPHOBIC OINTMENTS, HYDROPHILIC OINTMENTS, AND GELS IN RELATION TO DRUG FORMULATION STABILITY - Rachmat, Rd.Lutpi; Al Arif, Moh. Anam; Hidanah, Sri; Lokapirnasari, Widya Paramita (Jurnal Biosains Pascasarjana, 2024)
Povidone – iodine has antiseptic properties for wound healing. This research makes antiseptic preparations in semi-solid dosage form with different bases used. This research aims to find out whether the different bases in the formula used can affect its stability and how much it costs for each formula. Formula 1 with a hydrocarbon base, formula 2 with a hydrophilic base, formula 3 gel with a Na-CMC base. The stability of the three formulas was observed using the freeze - thaw method with different temperatures for 18 days of storage and observed organoleptically, homogeneity, spreadability, pH viscosity and then processed using one way ANOVA and I-MR control charts. The research results showed that the different bases in the formula had a significant effect on the spreadability, pH and viscosity values ​​with a significant value of 0.000. Differences in formula also affect organoleptic results and homogeneity. Formula 2 has the best stability based on the results of the tests carried out. In terms of costs, Formula 2 has greater raw material costs compared to Formula 1 and Formula 3. Keywords: Antiseptic, cost and stability